Bacterial cellulose-based composites for biomedical and cosmetic applications: Research progress and existing products. (1st December 2021) - Mbituyimana, Bricard; Liu, Li; Ye, Weiliang; Ode Boni, Biaou O.; Zhang, Kai; Chen, Jiachuan; Thomas, Sabu; Vasilievich, Revin Victor; Shi, Zhijun; Yang, Guang
Abstract: Bacterial cellulose (BC) is a promising unique material for various biomedical and cosmetic applications due to its morphology, mechanical strength, high purity, high water uptake, non-toxicity, chemical controllability, and biocompatibility. Today, extensive investigation is into the manufacturing of BC-based composites with other components such as nanoparticles, synthetic polymers, natural polymers, carbon materials, and biomolecules, which will allow the development of a wide range of biomedical and cosmetic products. Moreover, the addition of different reinforcement substances into BC and the organized arrangement of BC nano-fibers have proven a promising improvement in their properties for biomedical applications. This review paper highlights the progress in synthesizing BC-based composites and their applications in biomedical fields, such as wound healing, drug delivery, tissue engineering, and cancer treatment. It emphasizes high-performance BC-based materials and cosmetic applications. Furthermore, it presents challenges yet to be defeated and future possibilities for BC-based composites for biomedical and cosmetic applications. Highlights: The various production methods to construct BC-based composites are discussed. The synthesis of high-performance BC based-materials is reviewed. BC-based composites for biomedical and cosmetic applications are described. Existing products of BC-based composites are presented. Future challenges for applications of BC-based composites are discussed.